Determinan Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI): Pendekatan Human-Organization-Technology (HOT) Fit Framework - Harnowo, Sudi; Santoso, Budi; Suryani, Embun (E-Jurnal Akuntansi, 2021)
This study was conducted to examine and analyze the effect of the implementation of the Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) on user satisfaction and condition of organization, condition of organization on user satisfaction, the effect condition of organization and user satisfaction on net benefit. The population of this study were all 105 SAKTI users within the Ministry of Finance in West Nusa Tenggara Province and 43 samples with a random sampling technique. Partial Least Square Structural Equation Modeling (PLS-SEM) was used to process the data. The study revealed there are five positive and significant influences: first, information quality on user satisfaction, second, system quality on condition of organization, third, service quality on condition of organization, fourth, user satisfaction on net benefits, and condition of organization on net benefits. Keywords: SAKTI, HOT-Fit Framework, Net Benefits.